Reformasie as herstel van die ware diens van God: enkele aanwysers by Calvyn en Zwingli - Schulze, L.F. (Koers, 1998)
Reformation as restoration of the true service of God - some indicators in the work of Calvin and ZwingliIn this article an attempt is made to interpret the 16th century Reformation from a rarely mentioned, yet very real perspective, viz., as a restoration of the true service of God. It is indicated that the true service o f God is an overarching concept, encompassing more than simply an ecclesiastical reform, or a return to the Bible. Besides these aspects, true service o f God implies the renewal o f life with all its social, economical and political overtones, which cannot be discussed in full in an article. Data drawn from some works o f Calvin and Zwingli will hopefully prove the validity o f this perspective and offer Christians in the "new South Africa" thought-provoking ideas which should be put into action.